Synergistic combination of paclitaxel with novel non-hypercalcemic calcitriol analog EM1 against triple negative breast cancer cells: new mechanism of action - Guevara, Josefina Alejandra (2022)
Triple-negative breast cancer (TNBC) is currently treated with cy- totoxic drugs such as paclitaxel (PTX) since it lacks targeted ther- apies, although it shows limitations in extending patient survival. The known mechanism of action of PTX is binding to β-tubulin and inducing apoptosis. The vitamin D receptor (VDR) is expressed in different tissues, including TNBC. Calcitriol, its natural ligand, shows antitumor activity, but its usefulness is limited by the hypercalcemia it causes at antitumor doses. Reports suggest that PTX shows syn- ergism when combined with calcitriol. The aim of this work is to com- bine PTX and non-hypercalcemic VDR analogs synthesized by our group, to study the potential synergism of the calcitriol analog EM1 with the cytotoxic PTX. EM1 in combination with PTX (EM1+PTX), showed a synergistic effect on the viability of 4T1 and MDAMB231 TNBC cell lines (p<0.001), CI<1. In contrast, EM1+PTX showed an antagonistic (protective) effect on non-tumor mammary HC11 cells (p<0.001), CI>1 (viability assays by crystal violet staining, Chou-Ta- lalay method). In addition, (EM1+PTX) delayed the migration of 4T1 and MDAMB231 cells (p<0.001, wound closure assay). Interesting- ly, synergistic effects were lost when the Vitamin D Receptor (VDR) was silenced in 4T1 cells. Docking and molecular dynamics studies showed a direct interaction of PTX with the VDR by binding to the re- gion near AF-2, stabilizing the active conformation between the VDR and its natural ligands. Cell cycle analysis by flow cytometry showed that the percentage of cells in the sub G0/G1 phase induced by PTX is higher in wild-type than in VDR-silenced cells. These results sug- gest that combining EM1 with current chemotherapy could increase the therapeutic effect on the cancer cell and prevent cell damage on normal cells. This differential effect could decrease the adverse effects associated with chemotherapy, through a new mechanism of action never before described for PTX.